Sunday

February 1, 2015

February 1, 2015

Posted by **cot** on Thursday, March 10, 2011 at 10:27pm.

g(2) = 5, g′(2) = -3, g′(-6) = -3, h(2) = -6,

and h′(2) = 4.

- math -
**drwls**, Friday, March 11, 2011 at 6:24amh(2) = -6

f'(2) = g'[h(2)] = g'(-6) = -3

**Answer this Question**

**Related Questions**

physics - Consider the two observers O and O′ at the origins of the ...

College Physics - Use the relativistic coordinate transformation (x, y, z, t) &#...

PHY 2054 - Use the relativistic coordinate transformation (x, y, z, t) − (...

Calculus - A table of values for f,g,f′, and g′ are given in the ...

Calculus - A table of values for f,g,f′, and g′ are given in the ...

College Math - In Exercises 63–68, determine the length of the sides and the ...

geometry - ABCD is a parallelogram. Let C′ be a point on AC extended such ...

Math - Every point (x,y) on the curve y=log23x is transferred to a new point by ...

Differenctial equations - Use the change of variable x = exp(s) to recast the ...

calculus - Consider the interval I=[6,7.6]. Break I into four subintervals of ...